Informal Divorces Resulting from Online Gambling in Rural Indonesia: Legal Pluralism, Informal Authority, and Access to Justice - Saipudin; Kunhaniah Mabruroh; A.Nurtamim Amin; Dody Pratama; Ahmad Failasuf Nasuha (Legitima : Jurnal Hukum Keluarga Islam, 2026)
Purpose – This study examines why rural communities in Gunung Labahan Subdistrict, Way Kanan Regency, continue to practice cerai sirri (informal divorce) outside the religious court system and analyzes its socio-legal consequences for women and children through the perspective of legal pluralism. Design/methods/approach – A qualitative socio-legal approach was employed using qualitative legal and content analysis. Data were collected between January and March 2026 through in-depth semi-structured interviews, observations, and Focus Group Discussions (FGDs) involving 12 informants, including divorced couples, village religious leaders (modin), and officials from the Office of Religious Affairs (KUA). Data were analyzed using interactive thematic analysis. Findings – The findings reveal that informal religious authority remains more influential than formal legal institutions because it is perceived as socially accessible, culturally legitimate, and procedurally practical. The expansion of online gambling has intensified household conflicts and contributed to informal divorce. Limited legal literacy, financial constraints, geographical barriers, bureaucratic complexity, and fear of court procedures further discourage access to formal justice. Although socially accepted, cerai sirri creates legal, economic, administrative, and psychological vulnerabilities, particularly for women and children. Research implications/limitations – The study is limited to one rural district; therefore, its findings may not represent other socio-legal contexts in Indonesia. Nevertheless, this highlights the need for more accessible judicial services, stronger legal literacy, and inclusive family law policies. Originality/value – This study contributes to socio-legal and Islamic legal scholarship by demonstrating how legal pluralism and structural barriers to access to justice shape informal divorce practices and influence community legal behavior in rural Indonesia.